2021
DOI: 10.5565/rev/elcvia.1238
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of an RGB-D cameras performance and a stereo camera in relation to object recognition and spatial position determination

Abstract: Results of using an RGB-D camera (Kinect sensor) and a stereo camera, separately, in order to determine the 3D real position of characteristic points of a predetermined object in a scene are presented. KAZE algorithm was used to make the recognition, that algorithm exploits the nonlinear scale space through nonlinear diffusion filtering; 3D coordinates of the centroid of a predetermined object were calculated employing the camera calibration information and the depth parameter provided by a Kinect sensor and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…By relating Equation ( 8) and ( 12), the relation between the acceleration in terms of mass and torque can be formulated as shown in Equation (13).…”
Section: Skid-steering Model Of the Autonomous Rovermentioning
confidence: 99%
“…By relating Equation ( 8) and ( 12), the relation between the acceleration in terms of mass and torque can be formulated as shown in Equation (13).…”
Section: Skid-steering Model Of the Autonomous Rovermentioning
confidence: 99%
“…Volumetric view and cameras. During the design discussions, we found that the accuracy from state-of-the-art consumer RGBD cameras [13,31] is not sufficient for very small and translucent objects during parts of medical procedures. Thus, we use large 1920x1080 screens in addition to 3D scene reconstruction in our system.…”
Section: Design Decisionsmentioning
confidence: 99%
“…Corresponding changes occur at the same time to determine whether the opening and closing are in place, that is, the "double confirmation" of the switch position needs to be realized. At present, the research methods for the identification of the opening and closing positions of the isolation switch mainly include pressure sensor technology, micro switch technology, optical sensing technology, attitude sensor and intelligent image recognition technology (Rodriguez, 2021). Among them, image recognition technology mainly refers to the use of computer vision, pattern recognition and other technologies to extract features from the information in the image area to meet the information and visual needs of users in different scenarios (Zheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%